Evaluation of millets for physio-chemical and root morphological traits suitable for resilient farming and nutritional security in Eastern Himalayas - Layek, Jayanta; Rangappa, Krishnappa; Das, Anup; Ansari, Meraj A.; Choudhary, Sunita; Rajbonshi, Namrata; Patra, Sandip; Kumar, Amit; Mishra, Vinay K.; Ravisankar, Natesan; Kumar, Sunil; Hazarika, Samarendra; et al. (Frontiers in Nutrition, 2023)
Introduction: Millets are a nutritionally superior and climate-resilient short-duration crop and get a prominent place in cropping sequences around the world. They have immense potential to grow in a marginal environment due to diverse adaptive mechanisms. Methods: The experiment was conducted under an organic production system in the Himalayan foothills for three consecutive years by evaluating high-yielding varieties (HYVs) of different millets, viz., finger millet, foxtail millet, little millet, barnyard millet, proso millet, and browntop millet, along with local germplasms of finger millets (Sikkim -1 & -2, Nagaland -1 & -2) to identify the stable, high-yielding, and nutritionally superior genotypes suited for the region. Results: Among the various millets, finger millet, followed by little millet, and foxtail millet, had proven their superiority in terms of productivity (ranged between 1.16 to 1.43 Mg ha-1) as compared to other millets. Among different varieties of finger millets, the HYV VL-Mandua 352 recorded the highest average grain yield (1.43 Mg ha-1) followed by local line Nagaland-2 (1.31 Mg ha-1) and Sikkim-1 (1.25 Mg ha-1). Root traits like total root length, root volume, the average diameter of roots, and root surface area were significantly higher in finger millet genotypes (Nagaland-1, 2, and Sikkim-1) as compared to the rest of the millet lines. The different types of millets were found to be rich sources of protein, foxtail millet (SiA-3088: 12.3%), prosomillet (11.5%), and finger millets, (Sikkim-1 and Nagaland-2: 8.7%). Finger millet, Sikkim-2 recorded the highest omega-6 content (1.16%), followed by barnyard millet, VL-207 (1.09%). Barnyard millet recorded the highest polyunsaturated fatty acid (PUFA) content (1.23%), followed by foxtail millet variety SiA-3088 (1.09%). While, the local finger millet genotypes, Sikkim-1 and -2 recorded the highest histidine (0.41%) and tryptophan (0.12%) content, respectively,  Sikkim-1 and Nagaland-2 recorded the highest thiamine (0.32%) as compared to the HYVs. Conclusion: These findings recommend that finger millet has great potential in this Himalayan ecosystem under an organic production system, and apart from HYVs like VL Mandua-352, local germplasms, viz., Nagaland-2 and Sikkim-1, should also be promoted for ensuring food and nutritional security in this fragile ecosystem.